O DAIA, isso serve, em primeiro lugar, para a apropriação de territórios - SILVA, Rodrigo Mendes da (2009)
The research objective is to understand the city of Anápolis/GO and Agro-industrial District - DAIA, based on the puzzle of social relations, entangled for diverse citizens, in which the State, the employers and the local working class are detach. The Agro-industrial district is situated in Goiânia-Anápolis-Brasilia axle (had for the local forces as important axle, with considerable population contingent and flow of capitals, pointed as one of the main corridors of development in the country) that it possess considerable infrastructure and a well consolidated industrial park, with prominence geographic localization, in way to a junction of federal and state highways, railroads, being relatively equidistant to any point in the country. The main objective is to elucidate how the process of production and appropriation of the territory of Anápolis and DAIA took place, permeated by disputes, and through out of the voices and the speeches of the involved citizens, to show its levels of influence and the real beneficiaries of the territorial (re)ordering. For in such a way, we will support our analyses in the territory category capable to show the conflicts and contradictions, also using the analysis of the speech as methodological tool. First we will approach the recent occurred transformations in the dynamics of the economy of the state of Goiás and its insertion in the national and world-wide scene, where it can be observe an intensification of the industrial activities spread by the state, through the not concentrated politics it saw Districts Agroindustrial, and as the DAIA appears in this context. We will also make the analysis of interviews with the involved actors, as well as documentary sources in the search of the identification of hegemonic speeches mainly leaving of the elites. Finally, the DAIA and Anápolis will be boarded as a territory in permanent dispute, elucidating themselves the confusion of relations entangled there, confronting statistical data, and the de(construction) development historically linked to the development of the Agro-industrial District. We made the collection of data concerning the DAIA as well as pertinent bibliography readings in a qualitative and quantitative data and also available in public agencies as Secretariat of the Farm of the State of Goiás - SEFAZ, Secretariat of Planning - SEPLAN, Brazilian Institute of Geography and Statistics - IBGE, Institute of Applied Economic Research - IPEA, Ministry of the Work - TM, State University of Goiás, Federal University of Goiás, among others, in addition to interviews in fieldwork. As main references we use, among others, E. Chaveiro, T. Arrais, P. Bertran, B. Borges, N. Chaul, M. Mendonça, C. Raffestin, M. Saints, R. Haesbaert, R. L. Corrêa, M. C. Andrade, F. Perroux. D. Harvey, M. Foucault, J. Gómez, M. Pochmann, C. Furtado, R. Antunes. We will see as it is possible to identify a dominant speech in which the DAIA was the main responsible for the development of the city, as well as being a powerful generator of jobs, and as these affirmations are fragile and hey do not go beyond speech. This speech is effective in camouflage the political games, of the true movements in the production and appropriation of the anapolino territory and its District, omitting also the real beneficiary of all this process of (re)ordering territorial orchestrated by the capital